Microbiome structure variation and soybean’s defense responses during flooding stress and elevated CO2 - Coffman, Lauryn; Mejia, Hector D.; Alicea, Yelinska; Mustafa, Raneem; Ahmad, Waqar; Crawford, Kerri; Khan, Abdul Latif (Frontiers in Plant Science, 2024)
With current trends in global climate change, both flooding episodes and higher levels of CO2 have been key elements to impact plant growth and stress tolerance. Very little is known about how both factors can influence the microbiome structure and function, especially in tolerant soybean cultivars. This work aims to (i) elucidate the impact of flooding stress and increased levels of CO2 on the plant defenses and (ii) understand the microbiome diversity during flooding stress and elevated CO2 (eCO2). We used next-generation sequencing and bioinformatic methods to show the impact of natural flooding and elevated CO2 on the microbiome architecture of soybean plants' below-and above-ground organs. We used high-throughput rhizospheric extra-cellular enzymes and molecular analysis to understand microbial diversity in plant defense responses. Results revealed that bacterial and fungal diversity was substantially higher in combined flooding and eCO2 treatments than in non-flooding control. Microbial diversity was soil>root>shoot in response to flooding and eCO2. We found that sole treatment of eCO2 and flooding had significant abundances of Chitinophaga, Clostridium, and Bacillus. In contrast, the combination of flooding and eCO2 conditions showed a significant abundance of Trichoderma and Gibberella.Rhizospheric extra-cellular enzyme activities were significantly higher in eCO2 than flooding or its combination with eCO2. Plant defense responses were significantly regulated by the oxidative stress enzyme activities and gene expression of Elongation factor 1 and Alcohol dehydrogenase 2 in floodings and eCO2 treatments in soybean plant root or shoot parts. This work suggests that climatic-induced changes in eCO2 and submergence can reshape microbiome structure and host defenses, essential in plant breeding and developing stress-tolerant crops.